Ebola virus disease outbreak in Guinea: what effects on prevention of mother-to-child transmission of HIV services? - Niouma Nestor Leno; Alexandre Delamou; Youssouf Koita; Thierno Souleymane Diallo; Abdoulaye Kaba; Therese Delvaux; Wim Van Damme; Marie Laga (BMC, 2018)
Abstract Background An unprecedented epidemic of Ebola virus disease (EVD) affected Guinea in 2014 and 2015. It weakened the already fragile Guinean health system. This study aimed to assess the effects of the outbreak on Prevention of Mother-to-Child Transmission of HIV (PMTCT) services in 2014. Methods We conducted a cross-sectional retrospective study. Data was collected from 60 public health centers (30 in the EVD affected areas and 30 in the unaffected areas). The comparison of PMTCT indicators between the period before Ebola (2013) and during Ebola (2014) was done using the t- test for the means and the Chi-square test for the proportions. Results This study showed a substantial and significant reduction in the mean number of antenatal care visits (ANC) in the affected localities, 1617 ± 53 in 2013 versus 1065 ± 29 in 2014, p = 0.0004. This would represent 41% drop in health facilities' performance. On the other hand, in the unaffected localities, the fall was not significant. The same observations were made about the number of HIV tests performed for pregnant women and the number of HIV positive pregnant women initiating ARVs. The study also noted an increase in the proportion of women tested HIV+ but who did not receive ARVs (12% in 2013 versus 44% in 2014) and HIV+ pregnant women who delivered at home (18% in 2014 versus 7% in 2013). Conclusion This study showed that PMTCT services, which are one of the key services to improve maternal and child health, were affected in Guinea during this Ebola outbreak in 2014 compared to 2013.